EFEKTIVITAS MODEL PEMBELAJARAN SATUS PADA MATA PELAJARAN AKUNTANSI USAHA DAGANG - Kesuma, Ameliasari Tauresia (Dinamika Pendidikan, 2014)
Teachers use SATUS learning model which includes observing, asking, trying, practicing and communicating with other people, all materials are made in steps so students can interpret and discuss the material of Trading Business Accounting. The objective of the research was to know the effectiveness of SATUS learning model which involves the learning activities at class XII IS 3 as the controlled class and class XII IS 4 as the experimental class. It was a classroom action research of experiment type. The data were collected by field observations. Then, the data were analyzed by descriptive comparative analysis of mean different test. The result of the research showed that SATUS learning model effectively improved studentsâ learning outcomes. This model involves all senses, learning styles and multiple intelligences which makes students empathize with others and environment.Â